2007
DOI: 10.1262/jrd.18089
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of a Progesterone-Based Timed Artificilal Insemination Protocol after Follicular Fluid Aspiration Using the Ovum Pick-up Technique in Suckled Beef Cows

Abstract: Abstract. We conducted a progesterone-based timed AI protocol after follicular fluid aspiration using the ovum pick-up (OPU) technique to examine its applicability to the suckled beef cow. A total of 19 beef cows were randomly allocated to one of the following three groups based on the number of days postpartum: 13 to 60 days (Group A: suckled; early postpartum period, n=9), 61 to 150 days (Group B: suckled; mid postpartum period, n=6), or 151 to 281 days (Group C: non-suckled; prolonged open period, n=4) post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Our results suggest that the OPU-PRID-TAI protocol is applicable to early postpartum beef cows and that successive OPU sessions during early pregnancy in animals bred by TAI does not impair maintenance of pregnancy. We also demonstrated a high conception rate in suckled early postpartum cows treated with a similar OPU-PRID-TAI protocol in our previous study [14]. In the present study, we used a protocol in which a PRID was inserted for 9 days, PGF2α was administered two days before PRID removal and GnRH was administered 36 hours after PRID removal to minimize the risk of ovulation before GnRH administration.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Our results suggest that the OPU-PRID-TAI protocol is applicable to early postpartum beef cows and that successive OPU sessions during early pregnancy in animals bred by TAI does not impair maintenance of pregnancy. We also demonstrated a high conception rate in suckled early postpartum cows treated with a similar OPU-PRID-TAI protocol in our previous study [14]. In the present study, we used a protocol in which a PRID was inserted for 9 days, PGF2α was administered two days before PRID removal and GnRH was administered 36 hours after PRID removal to minimize the risk of ovulation before GnRH administration.…”
Section: Discussionmentioning
confidence: 66%
“…We previously reported that it is possible to attain high conception and production rates for embryos by IVP in Japanese Black cows within 60 days postpartum, regardless of resumption of ovarian activity at the onset of treatment, by applying an ovulation synchronization protocol in combination with the OPU technique on day 0 and placement of a progesterone releasing intravaginal device (PRID) from day 0 for 7 days [14]. However, suckling has been suggested to delay postpartum resumption of ovarian function in beef cows because the suckling stimulus exerts negative feedback on the hypothalamus [1].…”
mentioning
confidence: 99%
“…Complete uterine involution takes more time than ovarian function, and the uterus is usually not ready for the embryo to implant until approximately 5 weeks postpartum in cows. When the ovaries start functioning normally, and uterine involution becomes complete, some cows can conceive by artificial insemination (AI) after estrous detection or a timed AI protocol without estrous detection [ 3 , 4 , 5 , 6 , 7 , 8 ]. However, some other cows cannot get pregnant because the uterine environment is not yet ready to accept the embryo for implantation because of persistent intrauterine inflammation beyond the puerperium.…”
Section: Introductionmentioning
confidence: 99%
“…We previously obtained a high conception rate using a TAI protocol with progesterone and follicular aspiration on suckled or nonsuckled Japanese Black cows as early as 30 days postpartum [23,24]. However, detailed information on the effect of follicular aspiration at the onset of TAI on subsequent follicular growth has yet to be elucidated.…”
mentioning
confidence: 99%